수질유해물질에 대한 수질환경기준 설정체계 - 고대현; 정윤철 (한국물환경학회, 2005)
In these days, water environment is getting threatened by a variety of toxic pollutants discharged from industries. However, environmental standards and regulations in Korea may be in straitened circumstances to protect the water environment from it. Therefore, the purpose of this review is to compare the management state of the toxic substances in water environment and to present the framework for deriving water quality criteria in USA and Japan. To conserve the water environment from the toxic pollutants more efficiently, the following considerations could be suggested in standards and regulation in Korea. Firstly, there should be consistency of regulated pollutants in drinking water quality standard, water quality standards and permissible wastewater discharge standards. Secondly, in case of deriving the water quality standards, it is required to consider the conservation of the aquatic ecosystem as well as the protection of human health. Finally, it is indispensable to make risk-based approach in management of toxic pollutants in water environment